Patients with Acromegaly Presenting with Colon Cancer: A Case Series - Murray B. Gordon; Samer Nakhle; William H. Ludlam (Case Reports in Endocrinology)
Introduction. Frequent colonoscopy screenings are critical for early diagnosis of colon cancer in patients with acromegaly. Case Presentations. We performed a retrospective analysis of the incidental diagnoses of colon cancer from the ACCESS trial (ClinicalTrials.gov identifier: NCT01995734). Colon cancer was identified in 2 patients (4.5%). Case  1 patient was a 36-year-old male with acromegaly who underwent transsphenoidal surgery to remove the pituitary adenoma. After surgery, the patient underwent routine colonoscopy screening, which revealed a 40 mm tubular adenoma in the descending colon. A T1N1a carcinoma was surgically removed, and 1 of 22 lymph nodes was positive for metastatic disease, leading to a diagnosis of stage 3 colon cancer. Case  2 patient was a 50-year-old male with acromegaly who underwent transsphenoidal surgery to remove a 2 cm pituitary adenoma. The patient reported severe cramping and lower abdominal pain, and an invasive 8.1 cm3 grade 2 adenocarcinoma with signet rings was identified in the ascending colon and removed. Of the 37 lymph nodes, 34 were positive for the presence of tumor cells, and stage 3c colon cancer was confirmed. Conclusion. Current guidelines for colonoscopy screening at the time of diagnosis of acromegaly and at appropriate follow-up intervals should be followed.